CORRELATION ANALYSIS OF PHYSICAL FITNESS ON THE OPTIMIZATION OF MOTOR ABILITIES IN JUNIOR HIGH SCHOOL STUDENTS - Khoirudin Jazali, Muhammad; Aliriad, Hilmy; Da’i, Mohammad (Holistic Journal of Sport Education, 2026)
This investigation set out to explore how levels of physical fitness relate to the development of motor skills in students at the junior secondary school stage. To address the research question, a quantitative correlational framework was adopted. Through purposive sampling, 38 students from junior secondary schools were selected to participate. Data gathering relied on two measurement tools, namely the Indonesian Physical Fitness Test (TKJI) for assessing fitness components, and the Test of Gross Motor Development-3 (TGMD-3) for capturing motor skill performance. The statistical output pointed to a substantial positive association between fitness and motor competence among the participants, expressed by a correlation value of r = 0.78 (p < 0.01). When examined component by component, muscular strength emerged as the leading contributor to motor performance (r = 0.72), with cardiovascular endurance close behind (r = 0.68), then agility (r = 0.65), and finally flexibility (r = 0.58). Taken together, the evidence suggests that strengthening physical fitness is integral to maximising the motor capabilities of junior secondary school learners.